Employee Well-Being Profiles During COVID-19 Lockdown: A Latent Profile Analysis of French and UK Employees - Harju, Lotta K.; Rokka, Joonas; Lopes, Maíra Magalhães; Airoldi, Massimo; Raïes, Karine (Frontiers in Psychology, 2021)
The coronavirus pandemic, social distancing, and lockdown measures have had an impact on employee well-being. This study uses Latent Profile Analysis to examine subjective well-being among employees during the first lockdown based on a cross-national survey in UK and France (n = 652). We identify five distinct well-being profiles, namely Moderately positive (67%), Languishing (18%), Flourishing (8%), Mixed feelings (4%), and Apathetic (3%). The results showed that while some employees were suffering, others managed to thrive and cope with the stresses of the lockdown. We also found that the profiles could be distinguished by perceived changes in financial situation and physical health as well as experienced boredom. Our study complements prior studies that examine the relations between individual characteristics and well-being during the pandemic on a general level by showing that employee well-being under lockdown is not the same across the board.